Hak Kepemilikan Badan Usaha Milik Negara (BUMN) Kaitannya Dengan Kewajiban Zakat (Studi Pada Regulasi Zakat di Indonesia) - Pratama, Agung Tri; Zaki, Muhammad (ASAS, 2021)
In the zakah regulations in Indonesia, it is explained that zakah is an asset that must be issued by a Muslim or a business entity to be given to those who have the right to receive it in accordance with Islamic law. And the generality of the word “business entity” includes State-Owned Enterprises (BUMN), Regional-Owned Enterprises (BUMD), and Swata-Owned Enterprises (BUMS). In accordance with Islamic law, zakah assets is required for assets with the status of milk al-tâm (perfect ownership), which are owned by muzakkî in the form of individuals or business entities. The problem in this study is the ownership rights of State-Owned Enterprises (BUMN) and its relation to the obligation of zakah, which is known that the assets/shares owned by BUMN are assets owned by the state. This research is library research, using primary, secondary and tertiary legal data. In addition, this research is descriptive qualitative by using a juridical, philosophical, historical approach. After the data has been collected, the next step is to analyze the existing data using data reduction techniques, data presentation and drawing conclusions. Based on the available data, it is concluded that the right of ownership of State Owned Enterprises (BUMN) is perfect ownership (milk al-tâm) which is one of the obligatory objects of zakah.Keywords: Company Zakah, Ownership Rights, State Owned Enterprises (BUMN)